X-RAY AND PATHOMORPHOLOGICAL FEATURES OF PULMONARY DISORDERS IN PREMATURE NEONATES - Bortnyi, M.O.; Kramnoi, I.O.; Voronzhev, I.A.; Churilin, R.Yu. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine")
Analysis of x-ray postmortem pathomorphological comparison of 10 premature neonates allowed to identify hyaline membrane syndrome. Six of them developed neonatal pneumopathies (hyaline membrane diseases), 4 - hyaline membranes at pneumony. It has been confirmed the certain value of excessive ventilation respiratory volume in the pulmonary affection development mechanism.